2023
DOI: 10.3389/fsufs.2023.1175893
|View full text |Cite
|
Sign up to set email alerts
|

Tea polyphenols: extraction techniques and its potency as a nutraceutical

Abstract: Usually, polyphenols help address numerous health issues caused by oxidative stress. Tea is a popular beverage (rich in polyphenols) with abundant health promoting and disease prevention with great health-promoting and disease-prevention attributes, originating from the delicate, dried leaves of the Camellia sinensis plant. Tea has been proven to have health-boosting impacts like anti-inflammatory, anti-cancerous, anti-diabetic, and aids in weight loss. Cognitive impairment, also known as cognitive decline cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 210 publications
0
3
0
Order By: Relevance
“…The tea plant ( Camelia sinensis (L.) Kuntze) contains an abundance of bioactive compounds with antidepressant properties [ 21 ]. Horia et al [ 22 ] demonstrated that many different tea-derived polyphenols, namely flavan-3-ols (catechin, gallocatechin, epicatechin), flavonols (kaempferol, quercetin), and phenolic acids (gallic and chlorogenic acid), presented anti-inflammatory activity via down-regulation of nuclear factor kappa-light-chain-enhancer of activated B cells’ (NF-κB) signalling pathway and antioxidant activity, which can be vital to reduce the risk of depression [ 21 , 22 ]. An important preclinical study demonstrated a significant improvement in memory and cognition in animal models of neurodegenerative diseases.…”
Section: Bioactive Compounds From Plants As Antioxidant Anti-inflamma...mentioning
confidence: 99%
See 1 more Smart Citation
“…The tea plant ( Camelia sinensis (L.) Kuntze) contains an abundance of bioactive compounds with antidepressant properties [ 21 ]. Horia et al [ 22 ] demonstrated that many different tea-derived polyphenols, namely flavan-3-ols (catechin, gallocatechin, epicatechin), flavonols (kaempferol, quercetin), and phenolic acids (gallic and chlorogenic acid), presented anti-inflammatory activity via down-regulation of nuclear factor kappa-light-chain-enhancer of activated B cells’ (NF-κB) signalling pathway and antioxidant activity, which can be vital to reduce the risk of depression [ 21 , 22 ]. An important preclinical study demonstrated a significant improvement in memory and cognition in animal models of neurodegenerative diseases.…”
Section: Bioactive Compounds From Plants As Antioxidant Anti-inflamma...mentioning
confidence: 99%
“…An important preclinical study demonstrated a significant improvement in memory and cognition in animal models of neurodegenerative diseases. Phenolic consumption has been associated with increased cognitive function, and their administration may prevent cognitive decline [ 22 ].…”
Section: Bioactive Compounds From Plants As Antioxidant Anti-inflamma...mentioning
confidence: 99%
“…Green tea has gained widespread popularity due to its numerous health benefits attributed to the presence of polyphenols, which are known for their antioxidant and anti-inflammatory properties [1,2,3,4] Shaukat et al, 2023]. The extraction process of polyphenols from green tea is a complex phenomenon influenced by various factors, including temperature, time, solvent composition, and particle size [5] Bindes et al, 2019].…”
Section: Introductionmentioning
confidence: 99%